Allergic Diseases and Risk of Incident Dementia and Alzheimer's Disease. Issue 2 (17th October 2022) - Joh, Hee‐Kyung; Kwon, Hyuktae; Son, Ki Young; Yun, Jae Moon; Cho, Su Hwan; Han, Kyungdo; Park, Jin‐Ho; Cho, Belong
Abstract : Objective: To examine the associations between the allergic triad (asthma, allergic rhinitis, atopic dermatitis) and risk of dementia. Methods: Participants comprised 6, 785, 948 adults aged ≥40 years who participated in a national health examination in 2009 without any history of dementia before baseline. From 2009 to 2017, we prospectively investigated the associations between physician‐diagnosed allergic diseases and risk of incident dementia (all‐cause, Alzheimer's disease [AD], vascular dementia [VaD]) ascertained using national health insurance claims data. Results: During 8.1 years of follow‐up, 260, 705 dementia cases (195, 739 AD, 32, 789 VaD) were identified. Allergic diseases were positively associated with dementia risk. Compared with individuals without allergic diseases, multivariable hazard ratios (HRs) of all‐cause dementia were 1.20 (95% confidence interval [CI] 1.19–1.22) in those with asthma, 1.10 (95% CI 1.09–1.12) with allergic rhinitis, 1.16 (95% CI 1.11–1.21) with atopic dermatitis, and 1.13 (95% CI 1.12–1.14) with any of these allergies. Similarly, individuals with any of the allergic triad had a higher risk of AD (HR 1.16, 95% CI 1.14–1.17) and VaD (HR 1.04; 95% CI 1.01–1.06) than those without any allergic disease. As the number of comorbid allergic diseases increased, the risk of dementia increased linearly ( P trend ≤ 0.002). Compared with individuals without allergies, those with all three allergic diseases had substantially increased risk of all‐cause dementia (HR 1.54, 95% CI 1.35–1.75), AD (HR 1.46; 95% CI 1.25–1.70), and VaD (HR 1.99, 95% CI 1.44–2.75). Interpretation: Asthma, allergic rhinitis, and atopic dermatitis were significantly associated with increased risk of all‐cause dementia and subtypes, with dose–effect relationships with the severity of allergic diseases. ANN NEUROL 2023;93:384–397